Budgeting for health: some considerations - Shiva Kumar, A.K. (2005)
The announcement of the National Rural Health Mission and the commitment in the recent budget to increase allocations for health are necessary steps in the right direction to correct India's shockingly poor health record as national and state level strategies unfold over the coming months, a vigorous and informed public discussion is needed to create a national consensus for dramatically increasing investments in health with concurrent improvements in accountability and management of the health care system. Equally important is induction of a cadre of village-based health activists, all women, who will link communities to an upgraded public health system. These women should emerge as the missionaries dedicated to advancing health in India. Money, medicines and medical facilities will be meaningless without these missionaries. Finally, flexibility, innovation, focus, inclusion and openness must become essential features of the functioning of the National Rural Health Mission in its endeavour to provide good quality health care for all. - Reproduced.
Keywords: Budget - India; Health services - India; Health services